Designing a Freestanding Electrode of Intermetallic Ni-Sn Alloy Deposit as an Anode for Lithium-Ion and Sodium-Ion Batteries. Issue 4 (1st April 2023) - Bhar, Madhushri; Pappu, Samhita; Bhattacharjee, Udita; Bulusu, Sarada V.; Rao, Tata N.; Martha, Surendra K.
Abstract : Carbon fiber (CF)-based freestanding intermetallic Ni-Sn alloy is prepared by a facile one-pot electrodeposition method and used as an anode in lithium-ion batteries (LIB) and sodium-ion batteries (SIB). Unique fern leaves-like morphology with nanotubular channels of the Sn-rich deposit of Ni-Sn@CF diminishes the challenges of large volume changes with maximum capacity utilization from Sn. Furthermore, the electro-inactive Ni phase and conductive carbon fiber backbone provide mechanical flexibility and prevent particle agglomeration during alloying/de-alloying. Electrochemistry reveals that the deposit in LIB exhibits superior C-rate performance and long-term cycling stability with an initial capacity of 984 mAh g −1 at 500 mA g −1 current density and 580 mAh g −1 capacity at the end of 500 cycles. Besides, it delivers 220 mAh g −1 capacity at 150 mAh g −1 with 77% capacity retention over 300 cycles in SIBs. This work enlightens the metal current collector-free carbon fibre-based 3D electrode designing approach toward high-performance Li-ion and Na-ion storage capability.